Antecedents of the Marketing Mix and Brand Image on Willingness to Recommend - Winoto Tj, Hery; Felicia Melinda, Thong; ., Fushen (Dinasti International Journal of Economics, Finance & Accounting, 2024)
With the anticipated rise in the number of hospitals driven by population growth, increasing healthcare expenditure, and escalating lifestyle-related disease risks, the hospital industry is facing intensified competition. Patient recommendations play a crucial role in hospital marketing, heavily influenced by patient satisfaction with service quality and a hospital's positive image. However, many hospitals encounter challenges with patient reluctance to recommend. This study evaluates patient satisfaction and willingness to recommend, focusing on a new hospital in Tasikmalaya. The sample consisted of 300 outpatients over 18 years old who had been treated at least twice. Data were gathered through randomly distributed questionnaires and analyzed using PLS-SEM. The findings reveal that the marketing mix, brand image, and patient satisfaction significantly and positively impact willingness to recommend. While the marketing mix has a positive but not significant effect on patient satisfaction, brand image significantly enhances patient satisfaction. Additionally, the marketing mix and brand image positively and significantly influence willingness to recommend when mediated by patient satisfaction.